REVISITING RUBLICISTIC WORKS OF IVAN BAHRJANYI AND GEORGE ORWELL IN THE CONTEXT OF THE RUSSIAN-UKRAINIAN WAR - Kobuta, S. S. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
The article dwells on the peculiarities of the authors’ understanding of the national liberty in the definite historical circumstances. The aim of the paper is to provide the comparative analysis of the critical essays of Ivan Barhriany and George Orwell that would reflect the similarities and differences of the authors’ worldviews in the framework of totalitarianism and Soviet foreign and internal policies of the mid-XX century. The article argues that the historical and contextual background of the essays in question bring their ideas forward into the beginning of the XXI century and provide explanation to a number of events unfolding in Ukraine and the world right now. The paper compares the authors’ vision of “nationalism”, “patriotism”, and “national liberty” in the context of the writers’ consecutive background, mainly the colonial British upbringing of George Orwell versus the struggling for national recognition Ukrainian background of Ivan Bahriany. In particular, the paper focuses on the authors’ interpretations of the rights of the dependent nations to fight for their freedom. It observes the characteristics of the democratic world reaction on the liberation processes in the USSR provided by George Orwell and Ivan Bahrjany along with focusing on the imperial nature of the USSR domestic policy. The emphasis is made on the peculiarities of the national liberty realization in the totalitarian regime and on the problem of the national identity preservation in the totalitarian state, especially in the context of the manipulation if facts and terminology substitutions as in “patriotism” vs “nationalism” vs “fascism”, “national assimilation” vs “national extermination”. The article defines similarities and differences in the George Orwell and Ivan Bahrjany’s interpretation of the national liberty and its limitation factors in the given historical circumstances. At the same time, it brings forward certain analogies with the current events taking place in the context of the on-going Russian war against Ukraine.